Solar thermal energy collection by compound parabolic collector and its storage in a packed-bed system: numerical and experimental analysis - Barbosa, Eloiny Guimarães (2023)
The use of renewable energy sources is crucial for maintaining the sustainability of the planet, reducing reliance on finite resources, and mitigating the environmental consequences of fossil fuel combustion. Among the various avenues of solar energy utilization, solar thermal energy has gained increasing prominence. Thermal storage systems have significantly enhanced the reliability and predictability of solar systems. This study aimed to establish parameters, explore different dryer configurations, and highlight the importance of thermal energy storage methods. Additionally, the thermal and economic performance of a U-tube compound parabolic collector (CPC) was evaluated in a prototype. Different filling fluids (water, air, and thermal oil) within the evacuated tube and varying mass flow rates (0.007, 0.009, 0.014, and 0.021 kg s-1) were examined. In the final section, a numerical evaluation was conducted on a packed bed thermal energy storage (PBTES) system. The optimization of this system considered various heat storage materials (concrete, quartzite rock, and cast iron) and particle sizes (0.02, 0.03, and 0.04 m). The evaluated CPC collector demonstrated an optical efficiency of approximately 63.6%. The use of thermal oil as the filling fluid led to a higher average thermal efficiency (41.2%) compared to water (31.7%) and air (31.1%). The lowest evaluated mass flow rate resulted in the highest average thermal efficiency (41.2%). Regarding the PBTES analysis, the utilization of materials with lower thermal conductivity led to an increased temperature difference between the heat transfer fluid and the solid material. The configuration of multilayer materials had a significant impact on loading and unloading times, as well as on stored and released thermal energy. Among the cases evaluated, Case 9 exhibited the highest stored thermal energy (27.2 MJ) and demonstrated commendable charge (87.5%), discharge (80.5%), and exergy (70.5%) efficiencies. Clearly, the variability in particle diameter and material type had a substantial influence on stratification and heat transfer within the PBTES. Keywords: Environmentally friendly system. Evacuated U tube solar collector. Renewable and sustainable energy. Solar energy. Thermocline thermal storage system.